2016
DOI: 10.3329/bjar.v41i3.29710
|View full text |Cite
|
Sign up to set email alerts
|

Association of yield and yield related traits in aromatic rice (Oryza sativa L.)

Abstract: Sixty cross combinations of SakkhorkhoraR and IR58025A were studied in the experimental field of Bangabundhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Salna, Gazipur during July 2010 to November 2010, to assess the character association & contribution of characters towards grain yield in restorer lines. The correlation study revealed that days to first flowering showed significant positive relationship with seed yield per plant at genotypic levels. Days to maturity showed significant positive rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
3
3
0
Order By: Relevance
“…Total tillers/hill was positively and significantly correlated with effective tillers/hill, filled grains/panicle, 1000grain weight and grain yield/plant. A similar result was found by other researchers for effective tillers/hill (24,53) and for grain yield/plant (24,48) in previous experiments. Regarding effective tillers/hill, the correlation was highly significant and positive with filled grains/panicle, 1000-grain weight and grain yield/plant.…”
Section: Character Association Between Yield and Yield Contributing Traitssupporting
confidence: 91%
“…Total tillers/hill was positively and significantly correlated with effective tillers/hill, filled grains/panicle, 1000grain weight and grain yield/plant. A similar result was found by other researchers for effective tillers/hill (24,53) and for grain yield/plant (24,48) in previous experiments. Regarding effective tillers/hill, the correlation was highly significant and positive with filled grains/panicle, 1000-grain weight and grain yield/plant.…”
Section: Character Association Between Yield and Yield Contributing Traitssupporting
confidence: 91%
“…The indirect effect of days to 50 per cent flowering (0.10) and time to maturity (0.10) through number of panicles per plant was positive and low. Similar, indirect but high effect has been reported by Akhi et al (2016). Days to fifty percent flowering (0.15) and time to maturity (0.11) through number of grains per panicle also showed low positive indirect effect on single plant yield.…”
Section: Path Analysissupporting
confidence: 79%
“…The direct effects of number of grains per panicle (0.58), number of panicles per plant (0.46), and 1000 grain weight (0.56) were positive and high. Akhi et al (2016) and Sathisha (2015) reported similar findings for number of grains per panicle and thousand grain weight respectively. Negative but low direct effect was contributed by days to fifty per cent flowering and positive low direct effect by time to maturity.…”
Section: Path Analysismentioning
confidence: 53%
“…Roy et al, (2012) studied the variation in agro-morphological and grain quality traits among traditional and Basmati-type aromatic/quality rice and observed highest variation for grains per panicle followed by grain yield per plant. Akhi et al, (2016) reported that spikelet fertility status (%) do have high positive direct effect with grain yield.…”
Section: Resultsmentioning
confidence: 99%